Content of carbon, nitrogen, Ca/Na value in palsa massifs of the Northern Hemisphere - Vasil'chuk, Alla Constantinovna; Vasil'chuk, Yurij K (PANGAEA, 2024)
The palsa and lithalsa are reliable indicators of the presence of permafrost, especially on its southern border. The subject of the study is the consideration of the C/N ratio in the peat of the palsa and the soil and humus horizon of the lithalsa as a criterion for the separation of the palsa and lithalsa. The palsas near the Eletskaya settlement in the Bolshezemelskaya tundra and the lithalsas in the Southern Transbaikalia near the Preobrazhenka village and in the valley of the Sentsa in the Eastern Sayan are considered. Included in the discussion is the background of lithalsa and palsa research in Russia at the start of the 20th century. It was found that the nitrogen content in the surface layers of the lithalsa (0.45-1.73% in the valley of the Sentsa River and 0.47-2.01% near the Arachley Lake) is approximately in the same range as in the surface horizons of the palsa, regardless of the permafrost region. The results of the carbon and nitrogen content determination, as well as their ratios in the peat cover of the palsa, are summarized. In contrast to the lithalsa, the carbon content in the peat horizons of the palsa and flat-hummock peatlands is many times higher than the values obtained for both surface and buried organic horizons of the lithalsa. The value of C/N less than 13 has not been recorded for the peat cover of palsa; this indicator for lithalsa never exceeds 10-12.
Keywords: Bolshezemelskaya tundra; carbon content; carbon isotope composition; C/N ratio; Eletskaya settlement; Lithalsa; nitrogen content; Palsa; permafrost region; Preobrazhenka village; Sentsa River valley